Mechanically alignable and all-dispenser-printable device design platform for carbon nanotube-based soft-deformable photo-thermoelectric broadband imager sheets - Minami Yamamoto; Daiki Sakai; Yuto Matsuzaki; Leo Takai; Yukito Kon; Yuto Aoshima; Noa Izumi; Naoko Hagiwara; Hayato Hamashima; Daiki Shikichi; Junyu Jin; Qi Zhang; et al. (npj Flexible Electronics)
Abstract While photo-thermoelectric (PTE) sensors and their ultrabroadband monitoring facilitate non-destructive testing, their conventional fabrication is insufficient for high-yield integration. Specifically, PTE devices faced challenges in their crucial spatial-misalignment for separate fabrication processes per constituent. Herein, this work demonstrates mechanically alignable and all-dispenser-printable integration of carbon nanotube (CNT) functional PTE sensor devices by designing them with solution-processable ink-materials. This technique first accurately prints CNT channels, essential in PTE conversion, using higher-concentration inks, and integrates remaining constituents (dopants and conductive pastes) into single device structures at high-yield. This work further demonstrates that employing higher-concentration CNT inks, suitable for mechanical channel printing, also designs sensitive PTE sensors. These sensors serve stably as integrated devices on diverse functional substrates, facilitating ubiquitous non-destructive monitoring depending on features. Therefore, this work designs such CNT PTE integrated devices and the associated functional inspection appropriately for structures, sizes, and external environments (e.g., temperature and humidity) of monitoring targets.